Physicochemical Quality and Genotoxic Potential of Wastewater Generated by Canteen Complex - Dada, Ebenezer O.; Agu, Chioma M.; Akinola, Modupe O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Canteens generate high volumes of wastewater that should constantly be subjected to physicochemical and genotoxicity screening. In this study, the wastewater generated by a canteen complex was screened for physicochemical properties and genotoxic potential using standard procedures and Allium cepa chromosome assay. Results showed that the wastewater had total suspended solids, total dissolved solids, and total hardness concentrations of 120.70 mg/l, 554.50 mg/l, and 500.00 mg/l, respectively. The chloride concentration of the wastewater (7873.60 mg/l) was much higher than the recommended limit of 250 mg/l. The wastewater inhibited root growth in A. cepa at 0.1%, 1%, 10%, 25%, 50%, and 100% concentrations but promoted root growth at 2% and 5% concentrations. The wastewater was highly mitodepressive, with mitotic inhibition generally increasing with rising concentrations. The major chromosomal aberrations observed in A. cepa exposed to different concentrations of canteen wastewater were vagrant, sticky, and bridged chromosomes. No chromosomal aberration was observed in onion roots exposed to water (control). The differences in total chromosomal aberrations across wastewater concentrations were not statistically significant (P > 0.05). In view of these results, the practice of discharging untreated canteen wastewater into drainage canals may not be environmentally sustainable.